GLCCI1 single nucleotide polymorphisms in pediatric nephrotic syndrome - Cheong, Hae Il (2012)
BACKGROUND: Empiric steroid therapy is the first-line therapy for pediatric nephrotic syndrome, but treatment response is variable. There are few predictors of steroid-responsiveness, though evidence for genetic factors exists. Recently, single nucleotide polymorphisms (SNPs) were identified in the promoter region of glucocorticoid-induced transcript 1 gene (GLCCI1) which effect steroid-responsiveness in asthmatic patients. Independently, GLCCI1 was identified as a podocyte protein, loss of which disrupts the function of the glomerular filtration barrier. We therefore examined whether SNPs associated with the steroid-responsive expression of GLCCI1 might predict steroid-responsiveness in nephrotic syndrome. CASE-DIAGNOSIS/TREATMENT: A cohort of 211 pediatric patients with nephrotic syndrome and 102 controls were genotyped; among the cases, 117 were initial steroid responders while 94 did not respond to oral steroids. No statistically significant differences were noted among the groups, though there was a trend in comparing the small subgroups of steroid-responsive and non-responsive patients with biopsy proven minimal change disease. CONCLUSIONS: While larger cohorts are needed to ascertain the possibility of a small effect of GLCCI1 SNPs on steroid-responsiveness of nephrotic syndrome, the GLCCI1 SNPs associated with steroid responsiveness in asthmatic patients are unlikely to have a clinically actionable impact in pediatric nephrotic syndrome.